2020
DOI: 10.5468/ogs.20177
|View full text |Cite
|
Sign up to set email alerts
|

Cervical polyp: evaluating the need of routine surgical intervention and its correlation with cervical smear cytology and endometrial pathology: a retrospective study

Abstract: Objective To determine the frequency of premalignant and malignant lesions in cervical polyps in order to examine whether cervical polyps need to be removed routinely and also to appraise its association with cervical smear cytology and endometrial pathologies. Methods We retrospectively reexamined the hospital records of 299 cases over a period of 5 years. All patients were segregated into perimenopausal and postmenopausal groups according to their menopausal status. The groups were compared in terms of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…The length of hospital stay in the current study was 4 days (range, [4][5]. This was longer than that reported by Vieira et al [19] who reported a short hospital stay of 1 day (range, 1-3) in the minimally invasive group.…”
Section: Conflict Of Interestcontrasting
confidence: 58%
See 1 more Smart Citation
“…The length of hospital stay in the current study was 4 days (range, [4][5]. This was longer than that reported by Vieira et al [19] who reported a short hospital stay of 1 day (range, 1-3) in the minimally invasive group.…”
Section: Conflict Of Interestcontrasting
confidence: 58%
“…Cervical polyps may be indicative of cervical or endometrial pathologies. Recent studies have reported that cervical polyps were associated with premalignant lesions in 2% of cases, and more seriously, 0.3% were associated with malignant lesions [ 4 , 5 ]. Other common symptoms after supracervical hysterectomy are abnormal offensive discharge, chronic pelvic pain, and impaired sexuality.…”
Section: Introductionmentioning
confidence: 99%
“…Others believe that patients undergoing polypectomy in pregnancy have high risks of miscarriage or spontaneous premature delivery [7][8][9]. Although most cervical polyps are benign, malignant change can be found in 0.2-1.63% of cases in the general population [1,10,11]. In pregnant persons the risk of malignancy is not clear and limited reports have describe rare forms of cancerous cervical polyps [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Although most cervical polyps are benign, malignant change can be found in 0.2%-1.63% of cases in the general population. 1,10,11 In pregnant persons, the risk of malignancy is not clear and limited reports have describe rare forms of cancerous cervical polyps. [12][13][14] There is a lack of evidence to evaluate the risk for patients with cervical polyps and management to provide full information to patients on their chances of a healthy pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Others believe that patients undergoing polypectomy in pregnancy have high risks of miscarriage or spontaneous premature delivery [7][8][9]. Although most cervical polyps are benign, malignant change can be found in 0.2-1.63% of cases in the general population [1,10,11]. In pregnant persons the risk of malignancy is not clear and limited reports have describe rare forms of cancerous cervical polyps [12][13][14].…”
Section: Introductionmentioning
confidence: 99%